Association between the ferritin level and risk of gestational diabetes mellitus: A prospective cohort study. - Xiaomei Zhang; Lili Huo; Ning Yuan; Zhixin Wang; Xingyun Zhu; Dan Zhao; Jianbin Sun (PLoS ONE)
Objective Iron is increasingly recognized to influence glucose metabolism. However, evidence about the linkage between body iron stores and the risk of developing gestational diabetes mellitus (GDM) is still inconclusive. We aimed to prospectively investigate the association of serum ferritin concentrations with GDM. Methods We studied 847 women from Peking University International Hospital from December 2017 to March 2019. Serum ferritin concentrations were measured three times during pregnancy (gestational weeks 6-12, 24-28 and 32-34). GDM was diagnosed by a 75-g oral-glucose-tolerance test (OGTT) at 24-28 weeks' gestation. Logistic regression analyses were carried out to determine the influence of serum ferritin at the first and second trimester on the risk of developing GDM. Results Among 847 participants, 73 women (8.6%) developed GDM. The median (IQR) of serum ferritin concentrations were 50.6 (32.4-75.5) ng/mL at gestational weeks 6-12, 19.7 (12.0-28.4) ng/mL at gestational weeks 24-28 and 19.4 (11.4-27.2) ng/mL at gestational weeks 32-34. The median serum ferritin concentrations were all significantly higher in women with GDM than those without GDM at the first, second and third trimester. Ferritin concentrations were positively correlated with the risk of GDM; the adjusted OR (95% CI) for highest vs lowest quartile was 2.97 (1.36, 6.51) at the first trimester and 2.64 (1.26, 5.54) at the second trimester. Conclusions Elevated serum ferritin concentrations in the first and second trimester during pregnancy are both independently associated with increased risk of GDM.